Profil Psikuedukasi Self-Efficacy Dalam Perencanaan Karir Siswa Dan Implikasinya Terhadap Nilai Filsafat Pendidikan - Aryani, Yunita Dwi; Prasetya, Akhmad Fajar; Barida, Muya; Hartanto, Dody; Kumara, Agus Ria (CV. SINAR HOWUHOWU, 2025)
Based on the reality in the field, some students have difficulty making career plans that are in line with their stage of professional growth. This is the background of this research. Psychoeducation is the practice of providing psychological knowledge or education to individuals or groups to increase their self-efficacy in career planning. Adolescent career planning involves selecting the type of additional education they are interested in because it is considered a component of their career development. Furthermore, many vocational high school graduates still have difficulty choosing jobs and developing in their fields of specialization. Because their skills do not match the needs of business, industry, or entrepreneurship, vocational high school graduates continue to face challenges in finding meaningful work and starting their own businesses. And what are the implications for the philosophy of education? This study uses a quantitative descriptive research design. The tools used are a survey of self-efficacy and career planning for vocational high school students. Based on the research findings, the students' overall self-efficacy profile is in the high category, while their career planning profile is in the competent group. In addition, self-efficacy has an important role in students' career planning. Guidance and counseling teachers are advised to develop a unique self-efficacy psychoeducational program to enhance students' career planning skills by considering the elements included in this program that are in line with the educational philosophy.